Social Determinants of Health in Maternity Care: A Quality Improvement Project for Food Insecurity Screening and Health Care Provider Referral (Mary Ann Liebert, 2021)
Purpose: This quality improvement project evaluated implementation of social determinants of health screening and referral for food insecurity. Methods: Four obstetric providers used study-developed resources to screen and refer English-speaking patients (n=14) during clinic visits. Providers and patients completed post-visit questionnaires. Provider feedback informed improvements to the intervention approach for consecutive study shifts. Results: Providers and patients reported high satisfaction with encounters. Referrals were made for four patients. Challenges to implementation included resource organization, time constraints, and integration into clinic workflow. Conclusion: Processes for universal screening and tailored information provision are areas to continue to strengthen for establishing equitable health care.